IL11-mediated stromal cell activation may not be the master regulator of pro-fibrotic signaling downstream of TGFβ - Tan, Yunhao; Mosallanejad, Kenta; Zhang, Qingxiu; O’Brien, Stephen; Clements, Meghan; Perper, Stuart; Wilson, Sarah; Chaulagain, Sudiksha; Wang, Jing; Abdalla, Mary; Al-Saidi, Helen; Butt, Danyal; et al. (Frontiers in Immunology, 2024)
Fibrotic diseases, such as idiopathic pulmonary fibrosis (IPF) and systemic scleroderma (SSc), are commonly associated with high morbidity and mortality, thereby representing a significant unmet medical need. Interleukin 11 (IL11)-mediated cell activation has been identified as a central mechanism for promoting fibrosis downstream of TGFβ. IL11 signaling has recently been reported to promote fibroblast-to-myofibroblast transition, thus leading to various pro-fibrotic phenotypic changes. We confirmed increased mRNA expression of IL11 and IL11Rα in fibrotic diseases by OMICs approaches and in situ hybridization. However, the vital role of IL11 as a driver for fibrosis was not recapitulated. While induction of IL11 secretion was observed downstream of TGFβ signaling in human lung fibroblasts and epithelial cells, the cellular responses induced by IL11 was quantitively and qualitatively inferior to that of TGFβ at the transcriptional and translational levels. IL11 blocking antibodies inhibited IL11Rα-proximal STAT3 activation but failed to block TGFβ-induced profibrotic signals. In summary, our results challenge the concept of IL11 blockade as a strategy for providing transformative treatment for fibrosis.